Detection of Solids in a Flow Stream Using Ultrasonics and Advanced Algorithms - Seraj, Hossein (Curtin University, 2021)
Sand passing along gas production pipelines can cause major disruption to facilities and interrupt gas flow. This research focused on improving sand flow measurement in gas pipes. It provided an improved method to measure sand flow rate using commercial Acoustic Sand Detectors. Also it provided several methods to measure sand flow rate in gas pipes using ultrasonic sensors and various signal processing techniques which were more accurate than any other methods.